Mercaptopurine Treatment in an Adult Man with Orbital and Intracranial Rosai-Dorfman Disease - Valentina Arnao; Marianna Riolo; Giovanni Savettieri; Paolo Aridon (Case Reports in Neurological Medicine)
Background. Rosai-Dorfmann disease (RDD) is a rare, idiopathic non-Langerhans cell histiocytosis, affecting children and young adults, that commonly presents as painless, massive cervical lymphadenopathy with fever, weight loss, and polyclonal hypergammaglobulinemia. Cervical lymphadenopathy and extranodal involvement are the main presentations. On the contrary, ophthalmic involvement and localisation in the central nervous system are rare. Case Report. An old man was admitted to our hospital for first seizure. Brain imaging studies revealed on the left an extra-axial thickening of the dura mater with enhancement and perilesional oedema, infiltrating the sphenoorbital fissure and an isointense mass with enhancement in the orbital region with dislocation of the optic nerve. Pathological and immunohistochemistry examination of the bioptical specimen was consistent with a diagnosis of RDD. Treatment with levetiracetam and steroids was started obtaining only remission of seizures. Because of the patient refusal of the surgical debulking, therapy with mercaptopurine was started, stopping disease progression. Conclusion. So far, very few cases of extranodal RDD with multiple CNS lesions involving the orbital region have been described. Our case is significant because it is the first case in which the efficacy of mercaptopurine treatment has been documented in an adult patient with isolated ocular and intracranial RDD.